2017
DOI: 10.1080/1828051x.2017.1305874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary conjugated linoleic acid on the intestinal mucosal immunity of broiler chickens

Abstract: The effects of dietary conjugated linoleic acid (CLA) on the intestinal mucosal immunity of broiler chickens were investigated. A total of 96 1-day-old Arbor Acres male broiler chickens were assigned to two dietary treatments (0 and 1% CLA) with eight replicates/each of six chickens. The intestinal mucosal immune status of broiler chickens was evaluated at 21-day old. The jejunal mucosa SIgA level increased by 43.58% (p < .01) while its mRNA expression increased by 22.95% (p < .01). The broilers receiving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…CLA increased the SIgA mRNA and SIgA protein content in the jejunal mucosa. CLA treatment significantly increased PPAR γ expression in jejunum as well as lymphocyte proliferation, and the percent of T lymphocytes (CD8 + ) in Peyer's node of broilers ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…CLA increased the SIgA mRNA and SIgA protein content in the jejunal mucosa. CLA treatment significantly increased PPAR γ expression in jejunum as well as lymphocyte proliferation, and the percent of T lymphocytes (CD8 + ) in Peyer's node of broilers ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for the improved immune responses could be ingestion of immunomodulatory agents from the hedge itself; chickens are omnivorous and naturally explorative foragers (Brunberg et al, 2016), and it has been suggested that relatively modest changes in the nutrient composition of the diet can markedly affect the development of immune mechanisms (Williams et al, 2020). While detailing the exact composition of all the flora and fauna available in our hedge was beyond the scope of this study, some potential examples of immune-modulatory agents that may have contributed to this effect include willow leaf (Al-Fataftah and Abdelqader, 2013), phytochemicals, which are natural bioactive compounds that are derived from plants and incorporated into animal feed to enhance productivity (Lillehoj et al, 2018;Williams et al, 2020), polyunsaturated fatty-acids (Liu et al, 2017), and insects (Biasato et al, 2018;Benzertiha et al, 2020;Józefiak et al, 2020).…”
Section: Discussionmentioning
confidence: 99%